Lymph node metastasis related gene BICC1 promotes tumor progression by promoting EMT and immune infiltration in pancreatic cancer - Feilong Meng; Shuai Hua; Xuedong Chen; Nanfeng Meng; Ting Lan (BMC, 2023)
Abstract Background Pancreatic cancer (PC) is one of the most aggressive abdominal malignancies with a poor prognosis and it is urgent to find effective biomarkers for prediction. Although BICC1 expression is related to the survival, no evidence for its role in PC development has been found. Methods We used RNA-seq data to screen for molecular markers highly associated with lymph node metastasis. The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) public databases were used to analyze the expression and prognosis of Differential Expressed Genes (DEGs) in PC. R studio was used for visualization and functional analysis. Results BicC Family RNA Binding Protein 1 (BICC1) was a lymph node metastasis-related DEGs in PC patients. Our study found that BICC1 mRNA levels in the tumor tissue were significantly higher and associated with poorer prognosis. Enrichment analysis found that BICC1 was enriched primarily in the Epithelial Mesenchymal Transition (EMT) pathway. Using the ESTIMATE and CIBERSORT algorithms, we found that BICC1 was related to immune cell infiltration. As a regulator of multiple immune checkpoints, BICC1 was also involved in PC's immune response. Conclusions BICC1 has the potential to be a new marker in association with lymph node metastasis as well as immune infiltration of PC. In addition to being a prognostic indicator, it may also be a potential therapeutic target.